Raoultella Planticola Bacteremia Following Consumption of Seafood - Philip W Lam; Irving E Salit (Canadian Journal of Infectious Diseases and Medical Microbiology)
Raoultella planticola is a Gram-negative bacillus commonly found in water, soil and aquatic environments. There have only been 16 cases of R planticola infection documented in the literature to date. R planticola possesses the ability to convert histidine to histamine and can produce symptoms of scombroid poisoning when poorly prepared seafood is consumed in large amounts. The present report describes a case involving a 56-year-old woman who presented with R planticola bacteremia and symptoms consistent with cholangitis four days after consuming a seafood salad containing squid and octopus. She was successfully treated with intravenous ceftriaxone followed by oral ciprofloxacin. Recent chemotherapy, proton pump inhibitor use and altered biliary flow secondary to hepatic metastases may have been contributing factors to the pathogenesis of disease.